Molecular insights informing factors affecting low temperature anaerobic applications: diversity, collated core microbiomes and complexity stability relationships in LCFA-fed systems - Singh, Suniti; Keating, Ciara; Ijaz, Umer Zeeshan; Hassard, Francis (Elsevier, 2023)
Fats, oil and grease, and their hydrolyzed counterparts-long chain fatty acids (LCFA) make up a large fraction of numerous wastewaters and are challenging to degrade anaerobically, more so, in low temperature anaerobic digestion (LtAD) systems. Herein, we perform a comparative analysis of publicly available Illumina 16S rRNA datasets generated from LCFA-degrading anaerobic microbiomes at low temperatures (10 and 20 °C) to comprehend the factors affecting microbial community dynamics. The various factors considered were the inoculum, substrate and operational characteristics, the reactor operation mode and reactor configuration, and the type of nucleic acid sequenced. We found that LCFA-degrading anaerobic microbiomes were differentiated primarily by inoculum characteristics (inoculum source and morphology) in comparison to the other factors tested. Inoculum characteristics prominently shaped the species richness, species evenness and beta-diversity patterns in the microbiomes even after long term operation of continuous reactors up to 150 days, implying the choice of inoculum needs careful consideration. The generalised additive models represented through beta diversity contour plots revealed that psychrophilic bacteria RBG-13-54-9 from family Anaerolineae, and taxa WCHB1–41 and Williamwhitmania were highly abundant in LCFA-fed microbial niches, suggesting their role in anaerobic treatment of LCFAs at low temperatures of 10–20 °C. Overall, we showed that the following bacterial genera: uncultured Propionibacteriaceae, Longilinea, Christensenellaceae R7 group, Lactivibrio, candidatus Caldatribacterium, Aminicenantales, Syntrophus, Syntrophomonas, Smithella, RBG-13-54-9, WCHB1–41, Trichococcus, Proteiniclasticum, SBR1031, Lutibacter and Lentimicrobium have prominent roles in LtAD of LCFA-rich wastewaters at 10–20 °C. This study provides molecular insights of anaerobic LCFA degradation under low temperatures from collated datasets and will aid in improving LtAD systems for treating LCFA-rich wastewaters.
Keywords: Fat; oil; grease (FOG); LtAD; Inoculum selection; Dataset collation; 16S rRNA sequence collation; Correlation plot; Psychrophilic